Internalisasi Nilai Psikologi Perkembangan Islam melalui Program Tahfidz dalam Membentuk Karakter Remaja Tengah (13-17 Tahun) Era Digital di Yayasan Panti Asuhan Al Hayya Depok - Anis Siti Qayyummah; Utary Rahayu; Andrey Pramudia; Dika Habib Permana; Miftahul Huda (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to analyze the internalization of Islamic developmental psychology values through the Qur'an memorization (Tahfidz Al-Qur'an) program in shaping the character of middle adolescents aged 13–17 years in the digital era at Al Hayya Orphanage Foundation, Depok. Adolescence is a transitional stage characterized by significant physical, emotional, social, and spiritual changes. In the digital era, adolescents face various challenges, such as social media addiction, cyberbullying, declining social interaction, and moral degradation, all of which may affect character development. Therefore, strengthening character education based on Islamic values has become increasingly important. This research employed a qualitative approach using a case study method to gain an in-depth understanding of the phenomenon under investigation. Data were collected through observation, in-depth interviews, and documentation involving orphanage caregivers, Tahfidz instructors, and students at Al Hayya Orphanage Foundation, Depok. The findings indicate that the Tahfidz program plays a positive role in character formation through habituation, role modeling, spiritual guidance, and a supportive religious environment. From the cognitive perspective, students demonstrated improvements in discipline, concentration, responsibility, and self-regulation. Emotionally, they became more patient, better able to control their emotions, and experienced inner peace through intensive engagement with the Qur'an. Socially, the program fostered attitudes of mutual assistance, respect, empathy, and stronger social relationships among students.This study reveals that the Tahfidz program serves not only as a means of memorizing the Qur'an but also as an effective medium for internalizing the values of Islamic developmental psychology and fostering Qur'anic character among adolescents in facing the challenges of the digital era.